Vascular Access Surgery (IntechOpen, 2023)
Decision-making regarding the route of access to minimize procedural complications, especially in patients with unusual or complicated vascular anatomy, is extremely important for successful vascular access surgery. Several techniques for vascular access are widely disputed in the context of achieving optimal clinical outcomes. This book discusses various clinical aspects of vascular access to enrich our knowledge and understanding of the contemporary methodology and management of vascular access for a broad range of purposes. In four sections, this book examines the following topics: 1. Vascular Access: Methodology and Contemporary Management; 2. Vascular Access and Reparative Surgery; 3. Vascular Access Failure; and 4. Risk Stratification in Vascular Access.